Effectiveness and Safety of Cataract Surgery Pharmacological Support in Glaucoma Patients - S. V. Yanchenko; A. V. Malyshev; S. N. Sakhnov; G. Yu. Karapetov (Oftalʹmologiâ, 2018)
Purpose: To evaluate effectiveness and safety of cataract surgery pharmacological support (which include 0.5 % levofloxacin, 0.09 % bromfenac and preservative free polyvinylpyrrolidone and polyvinyl alcohol fixed combination instillations) in glaucoma patients. Patients and Methods: Standard ophthalmological examination, subjective discomfort level evaluation, tear film break up time, tear meniscus height measurement, index of xerosis, evaluation and ocular surface condition photoregistration were performed in 40 II «A» primary open-angle glaucoma patients, receiving hypotensive therapy, before and after phacoemulsification (Ph). All patients in the postoperative period received instillations: 0.5 % levofloxacin (4 times a day, 7 days), 0.1 % dexamethasone (3 times a day, 7 days), 0.09 % bromfenac (once a day, 30 days) and preservative free polyvinylpyrrolidone and polyvinyl alcohol fixed combination (3 times a day, 30 days). Control points were: examination before Ph, on 1, 7 and 30 days after Ph. Results: None cases of infectious or inflammatory surgery complications were recorded. The SD level was significantly increased on the 1 and 7 days after Ph, by the 30 day the SD level was significantly decreased, compared with a state on the 1 and 7 days. On the 1, 7, 30 days after Ph TFBUT significantly decreased. By the 30 day after Ph the TFBUT was significantly increased in compare with 1 and 7 days after operation. TMH changes after Ph had multidirectional character and in general were not significant throughout the observation, with a tendency to increase on the 1 and 30 days after surgery and to decrease on the 7th day. IX dynamics in compare with a state before Ph was not significant in all control points with a tendency to its increase on the 1 and 7 days after operation and to decrease on the 30th day. In general, pharmacological support of Ph was assessed by all patients as comfortable, there was no intolerance. Conclusion: The cataract surgery pharmacological support in glaucoma patients (including 0.5 % levofloxacin, 0.09 % bromfenac and preservative free polyvinylpyrrolidone and polyvinyl alcohol fixed combination instillations) showed: high efficiency (in prevention of infectious and inflammatory complications); safety by influence on the ocular surface; comfort of use.